PENGUATAN PENDIDIKAN KARAKTER BERBASIS ISLAM BAGI GURU PAI DI KAB. LAMPUNG SELATAN - JONI PUTRA; Aryan Danil Mirza. BR; Rima Yuni Saputri (Najah Bestari, 2023)
Education is one of the important means in shaping human beings into human beings with character. Character building will be realized if educators who become facilitators for students themselves have strong character and are based on Islamic values. The methods of implementing the dedication used include: (1) Workshop activities for delivering material related to the importance of Islamic-based character education to PAI teachers in South Lampung Regency; (2) Discussion/question and answer about the importance of Islamic-based character education. By this community service, it is hoped that PAI teachers in South Lampung Regency will have a deeper understanding of Islamic-based character education so that they can be applied in the learning process which hopes to be able to produce students with character, morality, and good morals.